7x+23x-8=6(5x+6)

Simple and best practice solution for 7x+23x-8=6(5x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+23x-8=6(5x+6) equation:



7x+23x-8=6(5x+6)
We move all terms to the left:
7x+23x-8-(6(5x+6))=0
We add all the numbers together, and all the variables
30x-(6(5x+6))-8=0
We calculate terms in parentheses: -(6(5x+6)), so:
6(5x+6)
We multiply parentheses
30x+36
Back to the equation:
-(30x+36)
We get rid of parentheses
30x-30x-36-8=0
We add all the numbers together, and all the variables
-44!=0
There is no solution for this equation

See similar equations:

| -2u+31=-7(u+2) | | 19v+v-11v+2v-8v=12 | | 29=x/9+2 | | 1+4n=-1+3n | | 8c+1=7c-14-2c= | | n+n/2+8=44 | | 26=x/9= | | x^2+x+4x-3=11 | | -28=-290+x | | −a=(2a2−3a+4) | | 76+u=626 | | 10n+25=-50 | | (1/4)(3t+27)=3/4(3t+15) | | -4-v=4v-4v-9 | | −a⋅(2a2=3a+4) | | 2n-11=n-5 | | (5*x)+(7*x)=180 | | −2(x+3)+5x=−39​ | | (⅕)x+3=2x-24 | | 3x-21/2=12 | | 26x+8+18x+8=48 | | 8y-3=1+2y | | x-50=3x-10 | | 3x+12x=30 | | -9=7(1+4m)+8(3-6m) | | 8-1/2p=3/2p-10= | | 3n=-41 | | -20=3(x-5)-8x | | x4+7=-2x4 | | 4x+6=1x+5. | | -(-8x+4)=5(2x+2) | | 6x-4=8x+15-5x |

Equations solver categories